Touch in the Time of Corona Reflections on Love, Care, and Vulnerability in the Pandemic - Veel, Kristin (De Gruyter, 2021)
The COVID-19 pandemic has hooked us all into digital networks as our access to cities, work and social gatherings is restricted and reconfigured. Weaving together cultural history, aesthetics, and urban and digital studies, this short volume reflects on how the possibilities for touch, touching and being touched, both physically and affectively, are reconfigured by the pandemic.